The Influence Of Emotional Intelligence And Job Stress On Organizational Commitment Through Job Satisfaction As A Mediating Variable At The Bali Office BASARNAS - Nyoman Sidakarya; Luh Komang Candra Dewi; I Putu Santika; Ni Luh Sili Antari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The objective of this study is to empirically examine the impact of emotional intelligence and occupational stress on organizational commitment, with the hypothesis that job satisfaction will serve as an intermediary variable between the predictor variables and the dependent variable. This investigation is being conducted at the Bali National Search and Rescue Agency (BASARNAS) Office. The population of this study comprised 130 employees of the Bali BASARNAS Office. The total sample size of the study was 130 individuals. The data analysis technique that was employed was path analysis, for which the data underwent testing to ascertain its validity, reliability, and classical assumptions. The findings indicated that emotional intelligence exhibited a positive and significant impact on job satisfaction and organizational commitment. Conversely, job stress demonstrated a negative and significant effect on job satisfaction and organizational commitment. Furthermore, job satisfaction exerted a positive and significant influence on organizational commitment. Job satisfaction positively influenced organizational commitment, which was facilitated by emotional intelligence. The present study hypothesizes that organizational commitment can act as a mediating variable on the influence of emotional intelligence on employee organizational commitment. It is predicted that job stress will have a negative effect on organizational commitment through job satisfaction at the Bali Basarnas Office. The present study sought to examine the potential mediating role of organizational commitment in the relationship between work stress and employee organizational commitment at the Bali Basarnas Office. The study posits that the leadership of the Bali Basarnas Office is expected to enhance emotional